2005
DOI: 10.1159/000087900
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Sequence Variations in the <i>ABCC6</i> Gene among Patients with Abdominal Aortic Aneurysm and Pseudoxanthoma Elasticum

Abstract: Abdominal aortic aneurysm (AAA) is characterized by dilatation of arterial walls, which is accompanied by degradation of elastin and collagen molecules. Biochemical and environmental factors are known to be relevant for AAA development, and familial predisposition is well recognized. A connective tissue disorder that is also associated with fragmentation of elastic fibers is Pseudoxanthoma elasticum (PXE). PXE is caused by mutations in the ABCC6 gene and mainly affects dermal, ocular and all vascular tissues. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 84 publications
(80 reference statements)
1
8
0
Order By: Relevance
“…Furthermore, a haplotype analysis was performed. ABCC6 sequence variations detected in selected exons in a subgroup of 53 patients were described in other publications by our group (Götting et al, 2004;Hendig et al, 2005;Schulz et al 2005a;Schulz et al 2005b). The diagnosis of PXE in all patients was consistent with the reported consensus criteria (Christiano et al, 1992;Lebwohl et al, 1994) taking into account that these consensus criteria do not provide golden standards for PXE diagnosis or the minimal diagnostic criteria of this disease.…”
Section: Patients and Controlssupporting
confidence: 83%
See 2 more Smart Citations
“…Furthermore, a haplotype analysis was performed. ABCC6 sequence variations detected in selected exons in a subgroup of 53 patients were described in other publications by our group (Götting et al, 2004;Hendig et al, 2005;Schulz et al 2005a;Schulz et al 2005b). The diagnosis of PXE in all patients was consistent with the reported consensus criteria (Christiano et al, 1992;Lebwohl et al, 1994) taking into account that these consensus criteria do not provide golden standards for PXE diagnosis or the minimal diagnostic criteria of this disease.…”
Section: Patients and Controlssupporting
confidence: 83%
“…This is so far the largest cohort of German PXE families which has been scanned for the complete ABCC6 gene. The present investigation is a follow-up study of our previous studies (Götting et al, 2004;Hendig et al, 2005;Schulz et al 2005a;Schulz et al 2005b) which now includes the complete analysis of all ABCC6 exons, the adjacent introns, the sequence of the putative proximal promoter and the haplotypes in a larger number of patients. Performing mutational analysis, we identified 42 different PXE mutations and among these 10 were novel.…”
Section: Novel Pxe Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…ABCC6 mutations were found in a minority of non-PXE patients (5/133) with abdominal aortic aneurysms (Schulz et al, 2005), but this was not statistically significantly different from healthy controls and could not be considered as a genetic risk factor for aortic aneurysms. Aorto-coronary aneurysm has also been reported (Heno et al, 1998) but seems not specific to PXE as it has also been reported in other PXE-like syndromes, such as beta-thalassemia (Farmakis et al, 2004).…”
Section: Clinical Expression Of the Vascular Pxe Phenotypementioning
confidence: 86%
“…It is, therefore, plausible that this gene might play a role also in AAA 57. One study investigated ABCC6 polymorphisms in 133 AAA patients and 910 controls, detected only five genetic variants (missense or silent amino acid variants) in the 133 AAA cases, and no significant associations 57…”
Section: Candidate Gene Studies (Tables I–v)mentioning
confidence: 99%